Enhanced Biogas Purification Using Low-Cost Adsorption and Absorption Techniques - Anceita Jepleting; Doricah Moraa; Dorcas Cheptoo; Achisa C Mecha (Sustainable Chemical Engineering, 2024)
The effectiveness of biogas as a source of energy is hampered by its low calorific value and equipment degradation due to corrosive impurities in raw biogas. Current purification techniques are tailored for large-scale applications; they consume a lot of energy, are expensive, and require high operating skills. In this study, adsorption and absorption at ambient conditions were explored for the removal of CO2 and H2S from biogas using NaOH and Ca(OH)2. Activated carbon (AC) derived from coconut shells and iron oxide from waste iron fillings were used as adsorbents. These waste-derived adsorbents are more affordable and easily accessible; moreover, their use contributes to effective waste management. The effects of biogas concentration, absorbent concentration, and adsorbent mass were evaluated. The synergistic effect of adsorption and absorption, recovery, regeneration, and reuse of the adsorbents were assessed. The adsorption capacity was 125.5 mg CO2/g AC and 58.2 ppm H2S/g iron oxide. The combined systems attained CO2 and H2S removal efficiencies of 98% and 100%, respectively, using iron oxide-NaOH; and > 95% and 100%, respectively, for the AC-iron oxide combination. The spent adsorbents were regenerated and reused at least twice. The CO2 adsorption was best described by the Yoon-Nelson model throughout the entire breakthrough profile, with an R2 value of 0.98 using AC. The low-cost sorbents used have great potential for biogas purification in small-scale systems.